The Effect of Blasting on Slope Stability at Pit Toka PT. Meares Soputan Mining - Alwi, Wahyudiansyah (ReTII, 2021)
PT. Meares Soputan Mining performs blasting activities to spread and form rock fragmentation, increase the productivity of digging tools and sometimes help shape slopes using the trim blasting method. The blasting produces residual energy in the form of ground vibrations that have the potential to disrupt the stability of the slopes on the eastern wall of Pit Toka stage 5. To get an idea of ​​the effect of the blasting, the study was conducted in March 2020. From observation and data processing, an equation shows the relationship between the blasting parameters to Peak Particle Acceleration, Peak Particle Acceleration to Maximum Horizontal Acceleration and Maximum Horizontal Acceleration to Strength Reduction Factor as slope stability parameters. The effect of blasting vibrations on the eastern slope of Pit Toka stage 5 is experiencing a decrease in the value of the critical Strength Reduction Factor on dry slope conditions and saturated slope conditions so that it must provide recommendations for blasting distances and maximum explosive charge per time delay, so that the maximum horizontal vibration acceleration value can be controlled and does not cause the slope to become unstable.